Causes, circumstances, and potential preventability of cardiac arrest in the young: insights from a state-wide clinical and forensic registry. Issue 12 (29th August 2022) - Paratz, Elizabeth D; van Heusden, Alexander; Zentner, Dominica; Morgan, Natalie; Smith, Karen; Thompson, Tina; James, Paul; Connell, Vanessa; Pflaumer, Andreas; Semsarian, Christopher; Ingles, Jodie; Parsons, Sarah; et al.
Abstract: Aims: The causes, circumstances, and preventability of young sudden cardiac arrest remain uncertain. Methods and results: A prospective state-wide multi-source registry identified all out-of-hospital cardiac arrests (OHCAs) in 1–50 year olds in Victoria, Australia, from 2019 to 2021. Cases were adjudicated using hospital and forensic records, clinic assessments and interviews of survivors and family members. For confirmed cardiac causes of OHCA, circumstances and cardiac history were collected. National time-use data was used to contextualize circumstances. 1319 OHCAs were included. 725 (55.0%) cases had a cardiac aetiology of OHCA, with coronary disease ( n = 314, 23.8%) the most common pathology. Drug toxicity ( n = 226, 17.1%) was the most common non-cardiac cause of OHCA and the second-most common cause overall. OHCAs were most likely to occur in sleep ( n = 233, 41.2%). However, when compared to the typical Australian day, OHCAs occurred disproportionately more commonly during exercise (9% of patients vs. 1.3% of typical day, P = 0.018) and less commonly while sedentary (39.6 vs. 54.6%, P = 0.047). 38.2% of patients had known standard modifiable cardiovascular risk factors. 77% of patients with a cardiac cause of OHCA had not reported cardiac symptoms nor been evaluated by a cardiologist prior to their OHCA. Conclusion: Approximately half of OHCAs in the young have a cardiac cause, with coronary disease and drug toxicity dominant aetiologies. OHCAs disproportionately occur during exercise. Of patients with cardiac cause of OHCA, almost two-thirds have no standard modifiable cardiovascular risk factors, and more than three-quarters had no prior warning symptoms or interaction with a cardiologist.